2015
DOI: 10.1007/s00221-015-4239-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased postural control in adolescents born with extremely low birth weight

Abstract: The survival rates of infants born preterm with extremely low birth weight (ELBW ≤ 1000 g) have gradually improved over the last decades. However, these infants risk to sustain long-term disorders related to poor neurodevelopment. The objective was to determine whether adolescents born with ELBW have decreased postural control and stability adaptation. Twenty-nine ELBW subjects performed posturography with eyes open and closed under unperturbed and perturbed standing by repeated calf vibration. Their results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…All the studies included underage participants, who were classified according to gestational age, regardless of birth weight and sex. Out of the 16 studies, eight provided the average gestational age per group ( 19 21 , 23 , 28 , 29 , 31 , 32 ); seven provided the intervals of gestational age which corresponded to each group ( 18 , 22 , 24 27 , 30 ), and one provided the data about the average gestational age of the preterm group, even though it did not provide data referring to the control group ( 33 ). The birth weight and sex of both groups was specified in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the studies included underage participants, who were classified according to gestational age, regardless of birth weight and sex. Out of the 16 studies, eight provided the average gestational age per group ( 19 21 , 23 , 28 , 29 , 31 , 32 ); seven provided the intervals of gestational age which corresponded to each group ( 18 , 22 , 24 27 , 30 ), and one provided the data about the average gestational age of the preterm group, even though it did not provide data referring to the control group ( 33 ). The birth weight and sex of both groups was specified in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies specified the intervention age, except for one ( 33 ), which only made reference to the age of the preterm group. Considering the last condition, it may be observed that seven studies were carried out during the first year of life of the participants ( 18 22 , 29 , 32 , 33 ), six were carried out from 3 to 10 years old ( 23 , 24 , 26 , 30 , 31 ), two were developed at the age of 13–17 years old ( 25 , 27 , 28 ) and one was carried out during the first year of life of the preterm infants group, but here the age of the control group was not specified ( 33 ). Out of the 16 studies included, six followed the evolution of the participants during a determined period of time; four were of a prospective nature ( 18 , 20 22 ), and two of a retrospective nature ( 32 , 33 ); the rest were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At eight to 10 years of age, it has also been found that the postural stability of ELBW children is inadequate compared to that of typically developing children of similar age . Finally, Peterson et al have provided further evidence of postural control deficits amongst ELBW teenagers (Petersen et al, 2015).…”
Section: Impact Of Preterm Birth On Postural Controlmentioning
confidence: 99%